Pretreatment of Woven Jute FRP Composite and Its Use in Strengthening of Reinforced Concrete Beams in Flexure - Tara Sen; H. N. Jagannatha Reddy (Advances in Materials Science and Engineering)
Environmental awareness motivates researchers worldwide to perform studies of natural fibre reinforced polymer composites, as they come with many advantages and are primarily sustainable. The present study aims at evaluating the mechanical characteristics of natural woven jute fibre reinforced polymer (FRP) composite subjected to three different pretreatments, alkali, benzyl chloride, and lastly heat treatment. It was concluded that heat treatment is one of the most suitable treatment methods for enhancing mechanical properties of jute FRP. Durability studies on Jute FRP pertaining to some common environmental conditions were also carried out such as effect of normal water and thermal aging on the tensile strength of jute FRP followed by fire flow test. The heat treated woven jute FRP composites were subsequently used for flexural strengthening of reinforced concrete beams in full and strip wrapping configurations. The study includes the effect of flexural strengthening provided by woven jute FRP, study of different failure modes, load deflection behavior, effect on the first crack load, and ultimate flexural strength of concrete beams strengthened using woven jute FRP subjected to bending loads. The study concludes that woven jute FRP is a suitable material which can be used for flexural upgradation of reinforced concrete beams.